Lisosys Linux-based network software management system - Magdolot, Beatrice N. (2010)
The use of Linux as an operating system for internet cafes is unpopular to the internet cafe industry. Though the familiarity of the masses to the Windows series operation system is a fector, the Linux operating system has garnered positive impression form testers. (Relevantive 2003). One of its advantages is lack of alternative programs running under the Linus operating system. This study allows internet cafes to create a Linux-based network that can be managed by the output system of this study. This study allows printing of application usage summaries and the transfers of sessions from one computer to the other. Also, this study also allows the restriction of application usage. Furthermore, this study allows the administrator to manage the users, user groups and applications of the network.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: Linux management; Network management; System management; Networking